2008
DOI: 10.1007/s11414-008-9126-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Improvement of Transitioning Young People in the Partnerships for Youth Transition Initiative: Findings from a Multisite Demonstration

Abstract: Prior research has indicated that young people with serious mental health conditions show poorer progress and greater challenges in the transition to adulthood, as reflected by lower rates of employment and postsecondary education, higher rates of criminal justice involvement, and greater interference in daily activities from mental health and substance use disorders. Little knowledge exists, however, regarding improvement on these indicators among young people enrolled in community-based transition support pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 24 publications
(23 reference statements)
1
35
0
1
Order By: Relevance
“…Therefore, the transition phase from basic education to vocational education is a significant period in the young adult's life. Difficulties in cognitive, social, and everyday life skills challenge coping with the transition as well (Floyd, Costigan, & Piazza, 2009;Haber, Karpur, Deschenes, & Clark, 2008).…”
Section: The Human-centered Approach Of Arranging Education For Peoplmentioning
confidence: 99%
“…Therefore, the transition phase from basic education to vocational education is a significant period in the young adult's life. Difficulties in cognitive, social, and everyday life skills challenge coping with the transition as well (Floyd, Costigan, & Piazza, 2009;Haber, Karpur, Deschenes, & Clark, 2008).…”
Section: The Human-centered Approach Of Arranging Education For Peoplmentioning
confidence: 99%
“…The participants across studies had various mental health disorders, namely severe emotional disturbance, schizophrenia, depression, first psychotic episode and autism spectrum disorder. The studies covered a range of study types including a systematic review (Taylor et al 2012), programme/model evaluations (Certo et al 2003;Styron et al 2006;Hillier et al 2007), randomized controlled designs (Killackey et al 2008;Burke-Miller et al 2012;Hagner et al 2012) and longitudinal designs (Karpur et al 2005;Haber et al 2008). See Table 1 for a full description of the nine selected studies.…”
Section: Descriptive Summarymentioning
confidence: 99%
“…Other multi-faceted intervention studies examined cohorts of youth participating in interventions covering multiple systems related to transition to adulthood, such as education, health care, community and vocational areas (Certo et al 2003;Karpur et al 2005;Styron et al 2006;Haber et al 2008). Specific programmes were identified in each study and key outcomes showed improvements in each programme.…”
Section: Descriptive Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…A growing consensus on this vision of mental health care for people with serious conditions is apparent in a series of recent policy statements (e.g., Altschuler et al 2009;Gagnon and Richards 2008;Institute of Medicine 2006) and federal funding initiatives (Frakera and Rangarajan 2009;U.S. Department of Health andHuman Services 2007, 2009), and is increasingly supported by research showing the benefits of care that is comprehensive, individualized, consumer-and/or family-driven, and community based (e.g., Bruns et al, in press;Daleiden et al 2006;Haber et al 2009;Sieler et al 2009). …”
Section: Introductionmentioning
confidence: 99%